PENGEMBANGAN ELEKTRONIK MODUL (E-MODUL) BERBASIS GUIDED INQUIRY PADA MATERI SUHU DAN KALOR UNTUK MENINGKATKAN LITERASI SAINS SISWA KELAS VII SMP/MTS - Sukarmin .; Mohammad Masykuri; Sri Andriani Andriani (Jurnal Penelitian Pendidikan IPA, 2021)
Scientific literacy skills are one of the needs of students in the 21st century which is experiencing very fast changes. This study aims to determine the characteristics, feasibility, and effectiveness of the guided inquiry-based E-temperature and heat module in improving students' scientific literacy. The learning steps in the E-module are structured with guided inquiry syntax which is integrated with scientific literacy indicators. The type of research used is research and development using the Borg and Gall model which is modified into 9 stages, namely: 1) preliminary research and information gathering, 2) planning, 3) initial product development, 4) initial product testing, 5) initial product revision. 6) limited trial phase, 7) second product revision, 8) operational trial, 9) final product revision. The data analysis technique used is descriptive analysis to describe the characteristics of the E-module, the feasibility analysis of the E-module based on the criteria score, and the analysis of the effectiveness of the E-module to improve students' scientific literacy based on the N-gain score. The results showed that the temperature and heat E-module has been successfully developed according to the guided inquiry model to improve students' scientific literacy, the guided inquiry-based temperature, and heat E-module is very suitable for use in learning, and the guided inquiry-based temperature and heat e-module is effective in improving the scientific literacy of students with a high category N-gain score.